CATALYST AND METHOD FOR SULFUR-TOLERANT CONVERSION CATALYST

A cobalt-molybdenum-based perovskite composite oxide catalyst, enhanced with rare earth and alkaline earth metals, addresses low catalytic activity in sulfur-resistant reactions by increasing specific surface area and stability, ensuring high performance even with low sulfur content.

JP7603834B2Active Publication Date: 2024-12-20CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023548991
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-27
Filing Date
2021-09-15
Publication Date
2024-12-20
Estimated Expiration
2041-09-15

AI Technical Summary

Technical Problem

Conventional cobalt-molybdenum-based sulfur-resistant conversion catalysts exhibit low catalytic activity and stability when exposed to raw material gases with low sulfur content.

Method used

A catalyst comprising a cobalt-molybdenum-based perovskite composite oxide supported on a carrier, with specific elements like rare earth metals and alkaline earth metals, enhancing the interaction between cobalt, molybdenum, and the carrier, thereby increasing the catalyst's specific surface area and stability.

Benefits of technology

The catalyst maintains high catalytic activity and stability even under harsh conditions with low sulfur content, offering improved performance and longevity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603834000002
    Figure 0007603834000002
  • Figure 0007603834000003
    Figure 0007603834000003
  • Figure 0007603834000004
    Figure 0007603834000004
Patent Text Reader

Abstract

The present invention relates to the field of sulfur-tolerant catalysts and discloses a catalyst, a method for producing the catalyst, and a method for producing a sulfur-tolerant conversion catalyst. The catalyst comprises a support and, supported on the support, molybdenum oxide, cobalt oxide, and a cobalt-molybdenum-based perovskite composite oxide. The cobalt-molybdenum-based perovskite composite oxide contains molybdenum, cobalt, element A, and element oxygen, where element A is one or more of a rare earth metal element, an alkali metal element, and an alkaline earth metal element. The catalyst of the present invention has high sulfur-tolerant catalytic activity even when used with a feed gas having a low H2S content.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Technical field] The present invention relates to the field of sulfur tolerant catalysts, and in particular to catalysts and sulfur tolerant catalytic conversion processes using said catalysts.

[0002] [Background technology] Sulfur-tolerant coal conversion is an important means for efficient coal utilization and is also the main method for hydrogen production at present, and catalysts are the core of the sulfur-tolerant coal conversion process. Compared with other types of catalysts, cobalt-molybdenum catalysts have the advantages of sulfur resistance, wide reaction temperature range, low cost, simple manufacturing process, etc., and are most widely used in equipment both at home and abroad.

[0003] Cobalt-molybdenum sulfur-tolerant catalysts are required to have high activity and high stability. In sulfur-tolerant conversion reactions using cobalt-molybdenum sulfur-tolerant catalysts, MoS2 is considered to be the main active component in the sulfur-tolerant conversion reaction, but when the H2S content in the feed gas is low, the catalytic activity of the cobalt-molybdenum sulfur-tolerant conversion catalyst decreases significantly.

[0004] Perovskite has many properties such as excellent electrical conductivity, magnetism, thermoelectricity, and piezoelectricity, and is inexpensive to manufacture, has thermodynamic and mechanical stability at high temperatures, and is an excellent conductor of oxygen ions and electrons under high temperature conditions. However, the specific surface area of ​​the currently manufactured perovskite-type sulfur-tolerant conversion catalyst is small, which severely limits the improvement of this type of catalytic activity.

[0005] Summary of the Invention [Problem to be solved by the invention] The object of the present invention is to provide a catalyst with high catalytic activity and stability, and a sulfur-tolerant conversion catalytic method using the catalyst, in order to solve the problem existing in the prior art that the catalytic activity of the sulfur-tolerant catalytic reaction is low, particularly for a raw material gas with a low H2S content.

[0006] [Means for solving the problems] In order to achieve the above object, one aspect of the present invention provides a catalyst comprising a support and, supported on the support, molybdenum oxide, cobalt oxide, and a cobalt-molybdenum-based perovskite composite oxide, wherein the cobalt-molybdenum-based perovskite composite oxide contains elemental molybdenum, elemental cobalt, element A, and elemental oxygen, and the element A is one or more of a rare earth metal element, an alkali metal element, and an alkaline earth metal element.

[0007] Preferably, the A element is one or more of La, Ce, Nd, Gd, Na, K, Mg, Ca, and Sr.

[0008] Preferably, the A element includes an A1 element and an A2 element, the A1 element being one or more of rare earth metal elements, and the A2 element being one or more of alkali metal elements and alkaline earth metal elements, preferably, the A1 element being one or more of La, Ce, Nd, and Gd, and the A2 element being one or more of Na, K, Mg, Ca, and Sr, and the molar ratio of the A1 element to the A2 element is preferably 1 to 99:99 to 1, and more preferably 1 to 9:9 to 1.

[0009] Preferably, the catalyst XRD spectrum exhibits a characteristic peak at 27.9±0.2°, preferably at 24.9±0.2°, 27.9±0.2° and 36.2±0.2°.

[0010] Preferably, the catalyst has a main reduction peak temperature of 600°C or higher, preferably 600 to 850°C in the H2-TPR spectrum.

[0011] Preferably, in a programmed temperature ramp vulcanization test of the catalyst, there are two or more, preferably three or more, adsorption / desorption peaks at 200° C. or higher.

[0012] In the catalyst, the content of the A element is preferably 0.4 mol or more and less than 1 mol, preferably 0.4 to 0.9 mol, and more preferably 0.5 to 0.9 mol, per 1 mol of the total content of the molybdenum element and the cobalt element.

[0013] Preferably, in the catalyst, the content of molybdenum element per 1 mol of the total content of molybdenum element and cobalt element is more than 0.4 mol and less than 1 mol, preferably more than 0.4 mol and less than 0.8 mol, more preferably 0.5 to 0.6 mol, and further preferably 0.55 to 0.6 mol.

[0014] Preferably, the support is aluminum oxide, silica, titanium dioxide, zirconium dioxide, magnesium oxide, nickel oxide, and a carbon-based support, or a composite support formed of two or more of these, and more preferably, aluminum oxide, or a composite support formed of aluminum oxide and one or more selected from silica, titanium dioxide, zirconium dioxide, magnesium oxide, nickel oxide, and a carbon-based support.

[0015] Preferably, in the catalyst, the support accounts for 30 to 90% by mass, preferably 30 to 80% by mass.

[0016] Preferably, the specific surface area of ​​the catalyst is 40 m 2 ·g -1 More than 50m, preferably 50m 2 ·g -1 More than 60m, preferably 60m 2 ·g -1 That's all.

[0017] A second aspect of the present invention provides a sulfur-tolerant catalytic conversion method, comprising a step of contacting CO in a raw material gas with water vapor in the presence of the above-mentioned catalyst of the present invention, wherein the raw material gas contains H2S, and the content of the H2S is 100 ppm or more, preferably 100 to 1500 ppm.

[0018] As a result of in-depth research, the inventors of the present invention have found that when a catalyst having a perovskite structure has an appropriate composition, it provides excellent catalytic performance while having high catalytic performance and high stability even under harsh conditions such as low sulfur and low water-gas ratio, compared to conventional catalysts.

[0019] Based on this, excess Mo and Co strongly interact with the perovskite body and the support, and there is a synergistic effect between the materials, which obviously increases the stability of the vulcanizate intermediate.

[0020] Therefore, in the present invention, in the process of supporting the cobalt-molybdenum-based perovskite composite oxide on the surface of the carrier, excess cobalt and molybdenum are added, so that part of the cobalt and molybdenum forms a perovskite composite oxide together with element A, part of the remaining cobalt and molybdenum adheres to the surface of the perovskite composite oxide, and the remaining part of the cobalt and molybdenum strongly interacts with the carrier, resulting in a strong synergistic effect between the perovskite structure and the carrier, and between the cobalt and molybdenum, so that the vulcanizate is stable after the catalytic vulcanization, and in the reaction, when the H2S content in the reaction gas is low, the catalyst has high stability and will not become inactive.

[0021] According to a preferred embodiment of the present invention, Al2O3 is a common carrier with a large specific surface area, and has abundant organic groups on its surface. When catalytic active components are dispersed on its surface, the surface will strongly interact with the active components. By using a suitable manufacturing method to support cobalt-molybdenum perovskite composite oxide on its surface, not only can the advantages of the perovskite catalyst be exerted, but the strong interaction between Al2O3 and the active components can be fully utilized, which significantly enhances the synergistic effect between the carrier and the perovskite composite oxide, and significantly improves the stability of the vulcanizate during the reaction with the sulfur-resistant catalyst.

[0022] [Effects of the Invention] The catalyst of the present invention has the following advantages:

[0023] (1) The catalyst of the present invention not only has the high specific surface area and high sulfur-resistant catalytic activity of perovskite catalysts, but also has high stability and a long catalytic life while maintaining high catalytic activity even under harsh conditions such as low sulfur content, because the cobalt and molybdenum in the catalyst strongly interact with the perovskite composite oxide and the support, and there is a synergistic effect between the support, the perovskite structure, and cobalt and molybdenum. In addition, the catalyst has a large specific surface area, which increases the amount of exposure to active sites and significantly increases catalytic activity.

[0024] (2) The catalyst of the present invention can be used as a sulfur-fixed type sulfur-tolerant conversion catalyst, and has high stability and a long catalyst life even under severe conditions such as when the sulfur content is low.

[0025] (3) The catalyst of the present invention has a relatively simple production process, is low cost, is easy to handle, and is suitable for large-scale industrial use.

[0026] BRIEF DESCRIPTION OF THE DRAWINGS FIG. 1 shows XRD spectra of catalysts produced in Example 1 of the present invention and Comparative Examples 3 and 4.

[0027] FIG. 2 is H2-TPR spectra of the catalysts produced in Examples 1 and 2 of the present invention and Comparative Example 3.

[0028] FIG. 3 shows TPS spectra of the catalysts produced in Example 1 of the present invention and Comparative Examples 3 and 4.

[0029] FIG. 4 shows XPS spectra of Mo species in the perovskite catalysts in Example 1, Example 13 and Comparative Example 3 of the present invention.

[0030] FIG. 5 is a Raman spectrum of Mo species in the perovskite catalysts in Example 1 of the present invention and Comparative Example 3.

[0031] [Mode for carrying out the invention] The range endpoints and any values ​​disclosed herein should be understood not to be limited to the precise range or value, but to include values ​​close to these ranges or values. In the case of numerical ranges, the values ​​between the endpoints of each range, between the endpoints of each range and the individual point values, and between the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be considered to be specifically disclosed herein.

[0032] One aspect of the present invention provides a catalyst comprising a support and, supported on the support, molybdenum oxide, cobalt oxide, and a cobalt-molybdenum-based perovskite composite oxide, wherein the cobalt-molybdenum-based perovskite composite oxide contains elemental molybdenum, elemental cobalt, element A, and elemental oxygen, and the element A is one or more of a rare earth metal element, an alkali metal element, and an alkaline earth metal element.

[0033] In the present invention, the molybdenum oxide may be any oxide of molybdenum, but is preferably an oxide obtained by roasting a molybdenum salt, such as MoO3, MoO2, or MoO, etc. The cobalt oxide may be any oxide of cobalt, but is preferably an oxide obtained by roasting a cobalt salt, such as Co3O4, CoO, etc. According to one preferred embodiment of the present invention, the molybdenum oxide is MoO3, and the cobalt oxide is Co3O4.

[0034] In the catalyst of the present invention, the A element as a structural assistant may be any A element component in any conventional perovskite complex oxide (represented by the general formula ABO3, in the case of a cobalt-molybdenum perovskite complex oxide, the B element is Co and Mo), and may be, for example, one or more of rare earth metal elements, alkali metal elements, and alkaline earth metal elements. The rare earth metal elements may be, for example, La, Ce, Nd, Gd, etc., the alkali metal elements may be, for example, Na, K, etc., and the alkaline earth metal elements may be, for example, Mg, Ca, Sr, etc. The A element is preferably a rare earth metal element and / or an alkaline earth metal element, more preferably La, Ce, Mg, Ca, Sr, etc.

[0035] According to a preferred embodiment of the present invention, the A element includes an A1 element and an A2 element, the A1 element being one or more of rare earth metal elements, and the A2 element being one or more of alkali metal elements and alkaline earth metal elements, preferably an alkaline earth metal element. For example, a cobalt-molybdenum perovskite composite oxide is represented by the general formula (A1): x (A2) 1-x It may be represented by BO3, where the B element is Co and Mo, and x may be 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, 0.3 or more, 0.35 or more, 0.4 or more, or 0.45 or more, and x may be 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, or 0.55 or less.

[0036] In a preferred case, the A1 element is one or more of La, Ce, Nd, and Gd, and the A2 element is one or more of Na, K, Mg, Ca, and Sr. By blending the A1 element and the A2 element, the catalytic activity and stability of the catalyst are further improved.

[0037] In a preferred case, the molar ratio of the A1 element to the A2 element is 1 to 99:99 to 1, preferably 1 to 9:9 to 1, and more preferably 1 to 2:2 to 1. By containing the A1 element and the A2 element in the above ratio, the catalytic activity and stability of the catalyst of the present invention are further improved.

[0038] The cobalt-molybdenum perovskite composite oxide is not particularly limited as long as it has a perovskite structure. Preferably, the content of the molybdenum element is more than 0.4 mol and less than 1 mol, more preferably more than 0.4 mol and less than 0.8 mol, even more preferably 0.5 to 0.6 mol, and even more preferably 0.55 to 0.6 mol, per 1 mol of the total content of the molybdenum element and the cobalt element. The cobalt-molybdenum perovskite composite oxide is, for example, AMo z Co 1-z In order to further improve the catalytic activity and stability of the catalyst, the molar ratio of molybdenum element to cobalt element in the catalyst may be preferably 0.5-0.6:0.4-0.5, and more preferably 0.52-0.56:0.44-0.48.

[0039] In order to ensure that the catalyst contains appropriate amounts of molybdenum oxide, cobalt oxide, and cobalt-molybdenum perovskite composite oxide at the same time to improve its catalytic activity and stability, the content of element A in the catalyst is preferably 0.4 mol or more and less than 1 mol, preferably 0.4 to 0.9 mol, and more preferably 0.5 to 0.9 mol, per 1 mol of the total content of molybdenum element and cobalt element in the catalyst.

[0040] In the present invention, theoretically, molybdenum element and cobalt element form perovskite complex oxide with element A in a total amount of 1:1 (molar ratio), and the remaining molybdenum element and cobalt element exist in the form of each oxide or both of the complex oxides. In view of the conventional detection means and the actual use effect of the present invention, without being limited by theory, in the present invention, as long as the molybdenum element and cobalt element contained in the catalyst are greater than the stoichiometric amount required to form a perovskite complex oxide with element A, it can be ensured that the catalyst contains molybdenum oxide (molybdenum oxide), cobalt oxide (cobalt oxide) and perovskite complex oxide, and the perovskite complex oxide does not need to be formed in a theoretical amount. The exact contents of molybdenum oxide, cobalt oxide and perovskite complex oxide do not affect the implementation of the present invention, and are all within the scope of the present invention.

[0041] According to the present invention, the support may be aluminum oxide, silica, titanium dioxide, zirconium dioxide, magnesium oxide, nickel oxide, and a carbon-based support, or a composite support formed of two or more of these. Preferably, the support is aluminum oxide, silica, titanium dioxide, and zirconium dioxide, or a composite support formed of two or more of these. Since molybdenum oxide, cobalt oxide, and cobalt-molybdenum perovskite composite oxide interact with the support, the support preferably contains an aluminum oxide support, and more preferably, the support is aluminum oxide, silica, titanium dioxide, zirconium dioxide, magnesium oxide, nickel oxide, and a carbon-based support, or a composite support formed of two or more of these.

[0042] Furthermore, in the catalyst of the present invention, there is no particular limitation on the form of the aluminum oxide support, and it may be one or more of α-Al2O3, β-Al2O3, γ-Al2O3, or amorphous aluminum oxide, as long as it can provide the desired catalytic activity. Since the specific surface area of ​​the catalyst is increased to improve the catalytic activity, the aluminum oxide support preferably contains at least a portion of γ-Al2O3. The aluminum oxide support in the catalyst of the present invention may be formed by an in-situ production method, but the catalyst of the present invention can also be obtained by supporting the aluminum oxide support.

[0043] In order to further improve the catalytic activity and stability, the support occupies 30 to 90 mass %, preferably 30 to 80 mass %, and more preferably 50 to 80 mass % of the catalyst.

[0044] According to the present invention, the specific surface area of ​​the catalyst is 40 m 2 ·g -1 More than 50m, preferably 50m 2 ·g -1 or more than 60m 2 ·g -1 More than 70m, preferably 70m 2 ·g -1 or more than 80m 2 ·g -1 More than 90m, preferably 90m 2 ·g -1 or more than 100m 2 ·g -1 or more, for example 40~180m 2 ·g -1 By including a carrier, the specific surface area of ​​the catalyst can be increased, and therefore the catalyst preferably includes a carrier.

[0045] In the present invention, the perovskite composite oxide, molybdenum oxide, cobalt oxide, cobalt-molybdenum perovskite composite oxide, and carrier contained in the catalyst may be characterized by a method such as X-ray diffraction (XRD). In a catalyst according to one preferred embodiment of the present invention, in the XRD spectrum, a characteristic peak at 25.5±0.2° indicates MoO3, a characteristic peak at 36.2±0.2° indicates Co3O4, and a characteristic peak at 27.9±0.2° indicates cobalt-molybdenum perovskite composite oxide. As for the carrier, taking the case of using an aluminum oxide carrier as an example, depending on the form of the aluminum oxide carrier, there may be a characteristic peak at one or more positions of 24.9±0.2°, 30.6±0.2°, 35.2±0.2°, 43.3±0.2°, 52.5±0.2°, and 57.5±0.2°.

[0046] According to the present invention, it has been revealed that the main reduction peak temperature of the catalyst is 600°C or higher, preferably 600 to 850°C, and more preferably 700 to 800°C in the TPR spectrum of the catalyst. It has been shown that most of the reduction temperatures of the reducible species inside the catalyst are 600°C or higher, and that there is a strong interaction force between the molybdenum oxide and cobalt oxide inside the catalyst and between the support and the perovskite composite oxide. In the present invention, the "main reduction peak temperature" is the peak temperature corresponding to the reduction peak with the largest peak area in the TPR spectrum of the catalyst.

[0047] According to the present invention, it is clear from the programmed temperature ramp vulcanization (TPS) spectrum of the catalyst that, in the programmed temperature ramp vulcanization test of the catalyst, there are two or more adsorption / desorption peaks at 200°C or higher, preferably three or more adsorption / desorption peaks, more preferably two or more adsorption / desorption peaks (e.g., three to five) in the range of 200°C to 600°C (preferably 200 to 500°C). After vulcanization, the catalyst of the present invention has a decomposition temperature of the vulcanizate inside the catalyst higher than 200°C as the temperature increases, and multiple adsorption / desorption peaks appear between 200°C and 600°C, indicating that the stability of the active components of the vulcanizate formed by vulcanization of the catalyst is high. According to one preferred embodiment of the present invention, in the programmed temperature ramp vulcanization test of the catalyst, there are adsorption / desorption peaks in the ranges of 250 to 270°C, 330 to 350°C, and 410 to 430°C.

[0048] The method for preparing the catalyst of the present invention may include, for example, gelling a precursor solution containing a carrier or a carrier precursor, a molybdenum-containing compound, a cobalt-containing compound, an A-element-containing compound and a complexing agent, and then drying and roasting the gel in sequence, where the A-element is one or more of a rare earth metal element, an alkali metal element and an alkaline earth metal element. In this preparation method, the carrier or the carrier precursor is directly used as the carrier or is used to form the carrier, and the molybdenum-containing compound, the cobalt-containing compound and the A-element-containing compound are jointly used to form the molybdenum oxide, cobalt oxide and cobalt-molybdenum-based perovskite complex oxide active components supported on the carrier. In a preferred case, the preparation of the carrier and the formation of the active material are prepared in one step (i.e., the carrier is synthesized by an in-situ preparation method), and a structure in which the molybdenum oxide, the cobalt oxide and the cobalt-molybdenum-based perovskite complex oxide are simultaneously supported on the carrier is obtained.

[0049] In the manufacturing method of the present invention, the molybdenum-containing compound, the cobalt-containing compound and the A element-containing compound are preferably soluble salts of the corresponding elements (such as nitrates, chlorides, sulfates, acetates, etc.). For example, the molybdenum-containing compound may be one or more of ammonium molybdate, molybdenum nitrate and molybdenum acetate, the cobalt-containing compound may be one or more of cobalt nitrate, cobalt chloride, cobalt acetate and cobalt carbonate, and the A element-containing compound may be one or more of lanthanum nitrate, cerium nitrate, neodymium nitrate, gadolinium nitrate, sodium nitrate, potassium nitrate, magnesium nitrate, calcium nitrate and strontium nitrate. Taking the aluminum oxide support as an example, the support or support precursor may be an aluminum oxide support, and the specific aluminum-containing compound may be one or more of aluminum isopropoxide, aluminum nitrate, aluminum acetate, pseudoboehmite and aluminum oxide.

[0050] The precursor solution can be prepared by dissolving the compound in water, and the specific method of mixing the compounds can be to dissolve the compounds in water in order as they are, or to directly mix the compounds using the aqueous solutions of the compounds. As a preferred mixing order, the carrier or carrier precursor, the molybdenum-containing compound, the cobalt-containing compound, the A element-containing compound, or the aqueous solutions thereof can be mixed in order, or the molybdenum-containing compound and the cobalt-containing compound can be simultaneously dissolved to form a molybdenum-cobalt-containing aqueous solution, and then mixed.

[0051] A specific example of the method for producing the precursor solution may include the following steps.

[0052] (1) The support or support precursor is added to deionized water and mixed uniformly.

[0053] (2) An aqueous solution of the A element-containing compound is added to the mixture obtained in step (1) and mixed uniformly.

[0054] (3) An aqueous solution of a molybdenum-containing compound and an aqueous solution of a cobalt-containing compound are each added dropwise to the mixture obtained in step (2) and mixed uniformly to obtain a new liquid mixture.

[0055] According to the present invention, the precursor solution further contains a complexing agent in order to promote the formation of a perovskite composite oxide. The complexing agent may be one or more of citric acid, EDTA, aminoacetic acid, acrylamide, lactic acid, tartaric acid, and hydroxybutyric acid. By adding a complexing agent to the precursor solution, the dispersibility of the active component on the support surface can be improved, and the organic group contained in the complexing agent chelates with the metal, promoting the interaction between the metals in the reaction, and promoting the formation of the perovskite phase and the improvement of the dispersion degree of the active component. Preferably, the amount of the complexing agent used is 1 to 4 mol, preferably 1 to 3 mol, and more preferably 1 to 2 mol, relative to 1 mol of the total amount of metal ions contained in the precursor solution. In addition, in the process of producing the precursor solution, the complexing agent is preferably added in sequence or simultaneously with the support or the support precursor, and for example, in the specific example of producing the precursor solution described above, citric acid is added in step (1).

[0056] In order to improve the catalytic activity and stability of the produced catalyst, the amount of the molybdenum-containing compound in molybdenum equivalent used is preferably more than 0.4 mol and less than 1 mol, more preferably more than 0.4 mol and less than 0.8 mol, even more preferably 0.5 to 0.6 mol, and even more preferably 0.55 to 0.6 mol, per 1 mol of the total amount of the molybdenum-containing compound in molybdenum equivalent and the cobalt-containing compound in cobalt equivalent in the precursor solution. The molar ratio of the molybdenum-containing compound in molybdenum equivalent to the cobalt-containing compound in cobalt equivalent is preferably 0.5 to 0.6:0.4 to 0.5, and more preferably 0.52 to 0.56:0.44 to 0.48.

[0057] In order to ensure that appropriate amounts of molybdenum oxide, cobalt oxide and cobalt-molybdenum based perovskite composite oxide are simultaneously contained in the produced catalyst, the amount of the A element-containing compound, calculated as the A element, used is preferably 0.4 mol or more and less than 1 mol, preferably 0.4 to 0.9 mol, and more preferably 0.5 to 0.9 mol, per 1 mol of the total amount of the molybdenum-containing compound, calculated as the molybdenum, and the cobalt-containing compound, calculated as the cobalt.

[0058] In the present invention, the method of forming the precursor solution into a gel is not particularly limited, and for example, the gel can be prepared by removing at least a part of the water in the precursor solution. Specific conditions for forming the gel may include a temperature of 40 to 90°C, preferably 60 to 80°C, more preferably 70 to 80°C, and a time of 4 to 24 hours, preferably 5 to 10 hours, more preferably 6 to 8 hours.

[0059] In the present invention, the drying and roasting method is not particularly limited, and may be performed using any equipment or conditions for producing a catalyst. In order to improve the catalytic activity and stability of the catalyst, the drying conditions may include a temperature of 60 to 200°C, preferably 80 to 150°C, more preferably 80 to 120°C, and even more preferably 80 to 110°C, and a time of 4 to 15h, preferably 5 to 15h, and more preferably 6 to 12h. The roasting conditions may include a temperature of 400 to 1300°C, preferably 500 to 900°C, and more preferably 600 to 900°C, and a time of 4 to 48h, preferably 6 to 12h, and more preferably 8 to 12h. By performing drying and roasting under the above conditions, the catalytic activity and stability of the produced catalyst can be further improved. In addition, the roasting temperature is preferably 600 to 700°C, in order to increase the specific surface area of ​​the catalyst and improve the catalytic activity and stability.

[0060] In a sulfur-tolerant catalytic conversion method according to a second aspect of the present invention, the method includes a step of contacting CO in a feed gas with water vapor in the presence of the catalyst of the present invention, the feed gas containing H2S, and the content of H2S is 100 ppm or more, preferably 100 to 1500 ppm.

[0061] As described above, the catalyst of the present invention is preferably used as a sulfur-tolerant conversion catalyst. When the catalyst of the present invention is used, a good catalytic effect can be obtained if the H2S content of the raw gas is 100 ppm or more (e.g., 100 to 2000 ppm or 300 to 2000 ppm). In particular, even when the H2S content of the raw gas is low (e.g., 1500 ppm or less, 1000 ppm or less, 800 ppm or less, 600 ppm or less, or 500 ppm or less), a good CO conversion rate can be obtained.

[0062] The present invention will now be described in detail with reference to examples.

[0063] Example 1 1.74 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C1. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0064] Example 2 0.64 mol of pseudoboehmite and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.13 mol of cerium nitrate was dropped into the solution and mixed uniformly. An aqueous solution of 0.13 mol of ammonium molybdate and 0.13 mol of cobalt nitrate was dropped into the solution and mixed uniformly to obtain a precursor solution. The precursor solution was then heated to 60°C to evaporate water for 10 hours and gradually gelled. The gel was baked at 120°C for 8 hours. The solid obtained by baking was roasted at 800°C for 12 hours to obtain catalyst C2. XRF measurement showed that the final aluminum oxide support accounted for 40% of the total mass of the catalyst, the molar ratio of La to the sum of Mo and Co was 1:2, and the molar ratio of Mo to Co was 1:1.

[0065] Example 3 0.48 mol of aluminum nitrate and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.21 mol of magnesium nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.25 mol of ammonium molybdate and 0.17 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C3. As a result of XRF measurement, the final aluminum oxide support accounted for 30% of the total mass of the catalyst, the molar ratio of Mg element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.6:0.4.

[0066] Example 4 0.91 mol of aluminum nitrate and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.11 mol of calcium nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.12 mol of ammonium molybdate and 0.1 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst A4. As a result of XRF measurement, the final aluminum oxide support accounted for 60% of the total mass of the catalyst, the molar ratio of Ca element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0067] Example 5 1.54 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.1 mol of ammonium molybdate and 0.1 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C5. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 1:1.

[0068] Example 6 1.76 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.12 mol of ammonium molybdate and 0.08 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C6. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.6:0.4.

[0069] Example 7 1.81 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.14 mol of ammonium molybdate and 0.06 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C7. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.7:0.3.

[0070] Example 8 1.95 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.13 mol of lanthanum nitrate was dropped into the solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the solution and mixed uniformly to obtain a precursor solution. The precursor solution was then heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The baked solid was roasted at 600°C for 8 hours to obtain catalyst C8. XRF measurement showed that the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La to the sum of Mo and Co was 1:1.5, and the molar ratio of Mo to Co was 0.55:0.45.

[0071] Example 9 1.96 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.15 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.097 mol of ammonium molybdate and 0.078 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C9. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:1.2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0072] Example 10 1.74 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 800°C for 8 hours to obtain catalyst C10. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0073] Example 11 1.74 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. The precursor solution was then heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 900°C for 8 hours to obtain catalyst C11. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0074] Example 12 0.87 mol of α-Al2O3 and 2 mol of citric acid were poured into deionized water and mixed uniformly to obtain a suspension. Then, an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the suspension and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the suspension and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C12. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0075] Example 13 1.48 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.05 mol of lanthanum nitrate and 0.05 mol of magnesium nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C13. As a result of XRF measurement, it was found that the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of the sum of La and Mg elements to the sum of Mo and Co elements was 1:2, the molar ratio of La to Mg elements was 1:1, and the molar ratio of Mo to Co elements was 0.55:0.45.

[0076] Example 14 1.52 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.05 mol of lanthanum nitrate and 0.05 mol of calcium nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C14. As a result of XRF measurement, it was found that the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of the sum of La and Ca elements to the sum of Mo and Co elements was 1:2, the molar ratio of La and Ca elements was 1:1, and the molar ratio of Mo and Co elements was 0.55:0.45.

[0077] Example 15 1.64 mol of pseudoboehmite and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.08 mol of lanthanum nitrate and 0.02 mol of calcium nitrate was dropped into the solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the solution and mixed uniformly to obtain a precursor solution. The precursor solution was then heated to 80°C to evaporate water for 6 hours and gradually gelled. The gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C15. XRF measurement showed that the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of the sum of La and Ca elements to the sum of Mo and Co elements was 1:2, the molar ratio of La and Ca elements was 4:1, and the molar ratio of Mo and Co elements was 0.55:0.45.

[0078] Example 16 0.25 mol of pseudoboehmite, 0.26 mol of metatitanic acid, and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.05 mol of lanthanum nitrate and 0.05 mol of calcium nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C, and the water was evaporated for 6 hours, gradually forming a gel. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst C16. As a result of XRF measurement, it was found that the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of the sum of La and Ca elements to the sum of Mo and Co elements was 1:2, the molar ratio of La and Ca elements was 1:1, and the molar ratio of Mo and Co elements was 0.55:0.45.

[0079] Comparative Example 1 1.48 mol of aluminum isopropoxide was poured into deionized water and mixed uniformly, and then an aqueous solution of 0.05 mol of lanthanum nitrate and 0.05 mol of magnesium nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst DC1. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of the sum of La element and Mg element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0080] Comparative Example 2 1.22 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.055 mol of ammonium molybdate and 0.045 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst DC2. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:1, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0081] Comparative Example 3 0.21 mol of ammonium molybdate and 0.17 mol of cobalt nitrate were dissolved in deionized water, and then the aqueous solution was used to impregnate 2 mol of pseudo-boehmite at an equal volume for 12 hours. After impregnation, the catalyst was baked at 120°C for 12 hours, and then roasted at 600°C for 8 hours to obtain catalyst DC3. XRF measurement showed that the final aluminum oxide support was 70% of the total mass of the catalyst, and the molar ratio of Mo to Co was 0.55:0.45.

[0082] Comparative Example 4 124.3g of α-Al2O3 and 2mol of citric acid were poured into deionized water and mixed uniformly to obtain a suspension. Then, an aqueous solution of 0.2mol of lanthanum nitrate was dropped into the suspension and mixed uniformly. An aqueous solution of 0.11mol of ammonium molybdate and 0.09mol of cobalt nitrate was dropped into the suspension and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6h and gradually gelled. The obtained gel was baked at 120°C for 12h. The baked solid was roasted at 600°C for 8h to obtain catalyst DC4. XRF measurement showed that the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La to the sum of Mo and Co was 1:1, and the molar ratio of Mo to Co was 0.55:0.45.

[0083] Comparative Example 5 2 mol of citric acid was poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.055 mol of ammonium molybdate and 0.045 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst DC5. As a result of XRF measurement, the molar ratio of La element to the sum of Mo element and Co element was 1:1, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0084] Comparative Example 6 2 mol of citric acid was poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst DC6. As a result of XRF measurement, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0085] Comparative Example 7 1.1 mol of aluminum isopropoxide and 2 mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. The precursor solution was then heated to 80°C to evaporate water for 6 hours and gradually gelled. The resulting gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst DC7. XRF measurement showed that the final aluminum oxide support was 70% of the total mass of the catalyst, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0086] Comparative Example 8 53.8g of α-Al2O3 and 2mol of citric acid were poured into deionized water and mixed uniformly, and then an aqueous solution of 0.11mol of ammonium molybdate and 0.09mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. The precursor solution was then heated to 80°C to evaporate water for 6h and gradually gelled. The gel was baked at 120°C for 12h. The solid obtained by baking was roasted at 600°C for 8h to obtain catalyst C14, which was named DC8. XRF measurement showed that the final aluminum oxide support was 70% of the total mass of the catalyst, and the molar ratio of Mo to Co was 0.55:0.45.

[0087] Comparative Example 9 1.638 mol of aluminum isopropoxide was poured into deionized water and mixed uniformly, and then an aqueous solution of 0.1 mol of lanthanum nitrate was dropped into the above solution and mixed uniformly. An aqueous solution of 0.11 mol of ammonium molybdate and 0.09 mol of cobalt nitrate was dropped into the above solution and mixed uniformly to obtain a precursor solution. Then, the precursor solution was heated to 80°C to evaporate water for 6 hours and gradually gelled. The obtained gel was baked at 120°C for 12 hours. The solid obtained by baking was roasted at 600°C for 8 hours to obtain catalyst DC9. As a result of XRF measurement, the final aluminum oxide support accounted for 70% of the total mass of the catalyst, the molar ratio of La element to the sum of Mo element and Co element was 1:2, and the molar ratio of Mo element to Co element was 0.55:0.45.

[0088] Test Example 1 XRD characterization was performed on the catalysts prepared in Example 1, Comparative Example 4, and Comparative Example 3 using an X'Pert3 Powder type X-ray diffractometer, with a Cu Kα target line (incident wavelength 1.54056A) in the scanning range of 0 to 90° and a scanning speed of 10 o / min, and the spectrum shown in Figure 1 was obtained.

[0089] As can be seen from FIG. 1, the XRD spectrum of the catalyst C1 obtained in Example 1 shows characteristic peaks at 24.9°, 25.5°, 27.9°, 30.6°, 35.2°, 36.2°, 43.3°, 52.5°, and 57.5°. The XRD spectrum of the catalyst DC4 obtained in Comparative Example 4 shows characteristic peaks at 21.6°, 24.9°, 27.9°, 30.6°, 43.3°, and 47.5°. The XRD spectrum of the catalyst DC3 obtained in Comparative Example 3 shows no obvious characteristic peaks. Among the above characteristic peaks, the characteristic peak at 25.5° indicates MoO3, the characteristic peak at 36.2° indicates Co3O4, the characteristic peak at 27.9° indicates a cobalt-molybdenum perovskite composite oxide, and the characteristic peaks at 21.6°, 24.9°, 30.6°, 35.2°, 43.3°, 47.5°, 52.5°, and 57.5°, etc. indicate Al2O3 support.

[0090] Similarly, the catalysts prepared in Examples 2 to 16 and Comparative Examples 2, 5 to 9 were characterized by XRD using the above method. The measurement results showed that the XRD spectra of the catalysts prepared in Examples 2 to 16 of the present invention were similar to that of the catalyst in Example 1, and all showed characteristic peaks of Co3O4, MoO3, cobalt-molybdenum perovskite composite oxide, and aluminum oxide support. On the other hand, the catalysts in Comparative Examples 1, 3, and 7 to 9 did not have a perovskite structure.

[0091] Test Example 2 FIG. 2 shows the results of measuring the H2-TPR spectra of the catalysts prepared in Examples 1 and 2 and Comparative Example 3 using a TP5080 adsorption apparatus manufactured by Tianjin Xianquan Co., Ltd.

[0092] From FIG. 2, it can be seen that the main reduction peak temperatures of the catalysts of Examples 1 and 2 were all in the range of 700 to 750°C, which was much higher than the main reduction peak temperature (less than 400°C) of the catalyst of Comparative Example 3, indicating that in the catalyst of the present invention, the interaction between the active component and the perovskite body and the aluminum oxide support is strong.

[0093] Test Example 3 Regarding the vulcanization behavior of the catalyst, a program temperature vulcanization (TPS) was performed using a TPS-5096 program temperature vulcanization device manufactured by Tianjin Xianquan Co., Ltd., and the results of measuring the vulcanization ability of the catalysts of Example 1 and Comparative Examples 3-4 are shown in FIG. 3. Specifically, the measurement method was as follows: first, 0.3 g of 20 mesh catalyst particles were weighed and placed in a reaction tube using a funnel, and the temperature was raised to 40°C at a rate of 10°C / min in an N2 atmosphere, kept at that temperature for 30 minutes, and then cooled to room temperature. The gas was switched to a 2.0% by volume H2S-98% by volume H2 atmosphere, and the temperature was raised to 900°C at a heating rate of 10 / min. The exhaust gas was detected by TCD.

[0094] 3, it was found that catalyst C1 of Example 1 had adsorption / desorption peaks at approximately 261° C., 340° C., 418° C., 647° C., and 672° C. Compared with catalyst DC3 of Comparative Example 3 and catalyst DC4 of Comparative Example 4, catalyst C1 of Example 1 exhibited clear H2S adsorption even in the high temperature region, while catalyst C1 of Comparative Example 3 exhibited H2S desorption in the high temperature region, indicating that the vulcanizate intermediate of catalyst C1 of Example 1 was stable.

[0095] Test Example 4 XPS characterization was performed on the catalysts prepared in Examples 1, 13, and Comparative Example 3. XPS characterization was performed using an AXIS-ULTRA DLD 1-line photoelectron spectrometer, employing a monochromatic Al-Kα target source. Before testing, the samples were pressed into sheets and 1×10 -8 The vacuum was applied under the condition of 100 Pa. To subtract the charge effect, the C1s (binding energy 284.6 eV) peak of contaminating carbon was used as the scaling standard.

[0096] From Figure 4, the binding energy of Mo species in catalysts C1 and C13 containing perovskite structure is obviously higher than that of Mo species supported on γ-Al2O3 catalyst, and the binding energy is further enhanced when alkaline earth metal is added to the perovskite structure, which indicates that the presence of perovskite causes temporary loss of electrons on the Mo surface, and the surrounding environment of the Mo species further enhances their interaction force, which is consistent with the TPR results.

[0097] Test Example 5 Raman spectroscopy was performed on the catalysts prepared in Example 1 and Comparative Example 3. The Raman spectroscopy was performed using a HORIBA LabRAM HR Evolution type confocal Raman spectrometer, using a 35 mV air-cooled He-Ne laser with an excitation wavelength of 532 nm. 0.1 g of powder sample (less than 100 mesh) was used for Raman characterization, and the 400-3000 cm -1 Spectra were recorded in the range of

[0098] From Figure 5, under the condition of the same amount of MoCo content, the catalyst DC3 of Comparative Example 3 does not have a characteristic stretching peak of Mo=O, and only a characteristic stretching peak of Co=O is present, which shows that the Mo species is highly dispersed inside the catalyst and some Co species are present as particles. On the other hand, the catalyst C1 of Example 1 has a characteristic peak of Mo=O, which shows that the Mo species is highly aggregated in this catalyst and highly dispersed on the γ-Al2O3 surface, which shows that the Mo species are highly aggregated on the perovskite surface, and the content of Co species on the γ-Al2O3 surface is significantly reduced, proving that some of the Co species are distributed on the surface of the perovskite mineral phase.

[0099] Test Example 6 A pressurized activity evaluation device was used to simulate industrial conditions, and the carbon monoxide concentration in the exhaust gas and its change were tested for the catalysts produced in the above Examples and Comparative Examples, to compare the performance of the catalysts, such as their conversion activity and stability, and to evaluate the overall performance of the catalysts.

[0100] In the pressurized activity evaluation device, the reaction tube is a stainless steel tube of Φ45×5mm, and has a heat-coupled tube of Φ8×2mm in the center. A certain amount of water is mixed with a water-gas ratio of 1.0, and after vaporization at a high temperature of 200℃, it is sent to the reaction tube together with the raw gas (raw gas composition in both tests: CO=45% by volume, CO2=2% by volume, H2S=0.15% by volume or 0.05% by volume, the remainder H2) to carry out the water-gas shift reaction, the reaction temperature is 260℃, and the exhaust gas after the reaction is analyzed by chromatography. The results are shown in Table 1.

[0101] Furthermore, the specific surface area of ​​each catalyst was measured using the BET method, and the results are shown in Table 1.

[0102] [Table 1]

[0103] From Table 1 above, it can be seen that the catalysts produced in the examples of the present invention have a higher CO conversion rate in the sulfur-tolerant conversion reaction than the comparative examples, and in particular, even when the H2S content in the raw gas is low, the CO conversion rate is good, and the catalytic activity in the sulfur-tolerant conversion reaction is good. The catalyst of the present invention can maintain a high CO conversion rate and stability even when the H2S content in the reaction gas fluctuates.

[0104] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, the technical solution of the present invention may be modified in a number of simple ways, including combining each technical feature in another suitable manner, and these simple modifications and combinations should also be regarded as the disclosed contents of the present invention, and all of them belong to the patent scope of the present invention. [Brief description of the drawings]

[0105] [Figure 1] 1 shows XRD spectra of catalysts produced in Example 1 of the present invention and Comparative Examples 3 and 4. [Diagram 2]2 shows H2-TPR spectra of catalysts prepared in Examples 1 and 2 of the present invention and Comparative Example 3. [Diagram 3] 1 shows TPS spectra of catalysts prepared in Example 1 of the present invention and Comparative Examples 3 and 4. [Figure 4] 1 shows XPS spectra of Mo species in perovskite catalysts in Example 1, Example 13 and Comparative Example 3 of the present invention. [Diagram 5] 1 shows Raman spectra of Mo species in perovskite catalysts in Example 1 of the present invention and Comparative Example 3.

Claims

1. The present invention comprises a carrier, and a molybdenum oxide, a cobalt oxide, and a cobalt-molybdenum-based perovskite composite oxide supported on the carrier, the cobalt-molybdenum-based perovskite composite oxide containing elemental molybdenum, elemental cobalt, element A, and elemental oxygen, A sulfur-tolerant conversion catalyst, characterized in that the element A is one or more of rare earth metal elements and alkaline earth metal elements.

2. 2. The sulfur tolerant conversion catalyst according to claim 1, wherein the A element is one or more of La, Ce, Nd, Gd, Mg, Ca, and Sr.

3. The A element is A 1 Elements and A 2 The A 1 The element is one or more of rare earth metal elements, 2 3. The sulfur tolerant conversion catalyst according to claim 1 or 2, wherein the element is one or more of the alkaline earth metal elements.

4. The sulfur tolerant conversion catalyst according to claim 3, wherein the A 1 element is one or more of La, Ce, Nd and Gd, and the A 2 element is one or more of Mg, Ca and Sr.

5. The sulfur tolerant conversion catalyst according to claim 3, wherein the molar ratio of the A 1 element to the A 2 element is 1-99:99-1.

6. The sulfur tolerant conversion catalyst according to claim 5, wherein the molar ratio of the A 1 element to the A 2 element is 1-9:9-1.

7. The sulfur-tolerant conversion catalyst according to any one of claims 1 to 6, which has a characteristic peak at 27.9±0.2° in an XRD spectrum.

8. A sulfur-tolerant conversion catalyst as described in claim 7, having characteristic peaks at 24.9±0.2°, 27.9±0.2° and 36.2±0.2° in the XRD spectrum.

9. H 2 The sulfur-tolerant conversion catalyst according to any one of claims 1 to 8, which has a main reduction peak temperature in a TPR spectrum of 600°C or higher.

10. The sulfur-tolerant conversion catalyst according to any one of claims 1 to 9, which has two or more adsorption / desorption peaks at 200°C or higher in a programmed temperature rise vulcanization test.

11. The sulfur-tolerant conversion catalyst according to any one of claims 1 to 10, wherein the content of the A element is 0.4 mol or more and less than 1 mol per 1 mol of the total content of the molybdenum element and the cobalt element in the sulfur-tolerant conversion catalyst.

12. The sulfur-tolerant conversion catalyst according to any one of claims 1 to 11, wherein the molybdenum content is greater than 0.4 mol and less than 1 mol per 1 mol of the total content of molybdenum and cobalt in the sulfur-tolerant conversion catalyst.

13. The sulfur-tolerant conversion catalyst according to any one of claims 1 to 12, wherein the support is aluminum oxide, silica, titanium dioxide, zirconium dioxide, magnesium oxide, nickel oxide, and a carbon-based support, or a composite support formed of two or more of these.

14. The sulfur tolerant conversion catalyst according to any one of claims 1 to 13, wherein the support accounts for 30 to 90 mass % of the sulfur tolerant conversion catalyst.

15. The specific surface area of ​​the sulfur-tolerant conversion catalyst is 40 m 2 ・g -1 The sulfur-tolerant conversion catalyst according to any one of claims 1 to 14.

16. The method comprises the step of contacting CO in a feed gas with water vapor in the presence of a sulfur-tolerant conversion catalyst according to any one of claims 1 to 15, The source gas is H 2 Contains S, and the H 2 A method for producing a sulfur-tolerant catalytic converter, characterized in that the S content is 100 ppm or more.

17. The sulfur tolerant conversion catalyst method according to claim 16, wherein the H 2 S content is 100 to 1500 ppm.

Citation Information

Patent Citations

  • Hydration-resisting and sulfur-resisting conversion catalyst and its preparation

    CN1087192C

  • JP1975064190A

  • Catalyst for catalytic reduction of nitrogen oxide

    JP1993076762A

  • Catalyst for catalytic reduction of nitrogen oxides

    JP1993245372A

  • Catalyst for catalytically reducing nox

    JP1993261289A